Fault Diagnosis Method for Operational Security Control System Based on Digital Twins - Wei HAN; Wenyan DUAN; Xingwei DU; Feng YAO; Weidong MA; Lei LIU (Zhongguo dianli, 2023)
The digital twin technology aims to break through the boundary between virtual and real, achieve organic integration of physical entities and virtual space through virtual real information links, and simulate the real-time state of physical entities. The security and stability control system (security control system) is the second line of defense to ensure the safe and stable operation of the power grid. If it refuses to act or malfunction due to a fault, it will cause serious harm to the operation of the power grid. Therefore, this paper proposes a fault diagnosis method for operational security control system based on digital twins. By analyzing the general operation strategies and possible failure links of the security control system, the digital twin system of the security control system is proposed. And a fault diagnosis model for security control system based on MPA-SVM is established. Finally, the validity and correctness of the proposed method is verified by using the operational data of the security control system to construct the sample datasets.